2021
DOI: 10.1111/famp.12639
|View full text |Cite
|
Sign up to set email alerts
|

Activism, Growth, and Empowerment of Israeli Parents of Children With Disabilities

Abstract: Traditionally, studies on parenting children with disabilities have focused mostly on experiences of stress. More recently, studies have turned to examining parental coping from the perspective of strength, focusing on the ability to achieve growth and empowerment. Most studies, however, have not examined parental activism as a coping mechanism. Based on the Double ABCX Model of Family Adjustment and Adaptation, this study, conducted in Israel, assessed the adequacy of a theoretical model linking stress, copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, according to STM, the augmentation of health empowerment at the individual level among spouse carers has the potential to have a positive impact on the HRQOL of older individuals with disabilities. However, the current body of research on carer empowerment has predominantly directed its focus toward enhancing caregiving skills, often overlooking the imperative aspect of prioritizing the well‐being and health empowerment of the caregivers themselves (Geva & Werner, 2021; Sakanashi & Fujita, 2017). Consequently, a significant gap exists in the comprehensive exploration of the direct influence of caregivers' health empowerment on their own HRQOL, as well as the effect of health empowerment among spouse carers on the HRQOL of older individuals with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, according to STM, the augmentation of health empowerment at the individual level among spouse carers has the potential to have a positive impact on the HRQOL of older individuals with disabilities. However, the current body of research on carer empowerment has predominantly directed its focus toward enhancing caregiving skills, often overlooking the imperative aspect of prioritizing the well‐being and health empowerment of the caregivers themselves (Geva & Werner, 2021; Sakanashi & Fujita, 2017). Consequently, a significant gap exists in the comprehensive exploration of the direct influence of caregivers' health empowerment on their own HRQOL, as well as the effect of health empowerment among spouse carers on the HRQOL of older individuals with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lower levels of empowerment may be an indication of social disengagement among individuals with a disability, according to findings from another study that found an association between unmet needs and empowerment levels (Dubuc et al, 2011). As a result, the empowerment of older individuals with disabilities may be essential because it may transform their self-concept from that of a powerless victim to that of a capable individual and thus, improve their HRQOL (Geva & Werner, 2021). Despite this, research quantifying the impact of health empowerment on HRQOL among individuals with disabilities remains scarce.…”
mentioning
confidence: 99%